1970
DOI: 10.1210/endo-87-6-1129
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Bone Resorption by Acetazolamide in the Rat1

Abstract: The carbonic anhydrase inhibitor, acetazolamide, has been found to elicit a hypocalcemic response in acutely nephrectomized rats. This effect cannot be attributed to changes in pCCh, pH citrate, phosphate or protein. Administration of acetazolamide to parathyroidectomized-nephrectomized rats has been shown to inhibit the hypercalcemic response to parathyroid extract and dibutyryl cyclic 3',5'-AMP. The hypercalcemic response to epinephrine was not inhibited in the same preparation. These data are consistent wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0
2

Year Published

1974
1974
1996
1996

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 25 publications
0
36
0
2
Order By: Relevance
“…Acetazolamide blockade ofcarbonic anhydrase, an enzyme present in rat osteoclasts, prevents PTHstimulated bone resorption in rats (30). The hypercalcemic response of rats to dibutyryl cyclic 3'5'-AMP is also blocked by acetazolamide, suggesting that the final mediator ofPTH-stimulated bone resorption is the local pH environment (31). In addition, recent experiments by Martin et al (32) have demonstrated that both the uptake and biological effect of PTH in an isolated, perfused canine-bone preparation is enhanced by acidosis.…”
Section: Discussionmentioning
confidence: 97%
“…Acetazolamide blockade ofcarbonic anhydrase, an enzyme present in rat osteoclasts, prevents PTHstimulated bone resorption in rats (30). The hypercalcemic response of rats to dibutyryl cyclic 3'5'-AMP is also blocked by acetazolamide, suggesting that the final mediator ofPTH-stimulated bone resorption is the local pH environment (31). In addition, recent experiments by Martin et al (32) have demonstrated that both the uptake and biological effect of PTH in an isolated, perfused canine-bone preparation is enhanced by acidosis.…”
Section: Discussionmentioning
confidence: 97%
“…Second, acid-secreting gastric and urinary cells also contain numerous mitochondria and very high carbonic anhydrase activity in the cytosol (1,26) as does the osteoclast (2,14,15,43). Inhibition of carbonic anhydrase activity prevents bone resorption in organ culture (28) and affects calcium metabolism in the intact animal (46). Genetic deficiency in carbonic anhydrase activity has recently been shown to be associated with a particular form of osteopetrosis, combining impaired osteoclastic resorption, and renal tubular acidosis (39).…”
Section: Discussionmentioning
confidence: 99%
“…× 9,000. tion areas was regarded as indicative of a low pH at these sites (31). Third, carbonic anhydrase, an enzyme associated with several acid-secreting epithelia, was demonstrated to be involved in bone resorption (28,46) and to be specifically concentrated in osteoclasts (2,14,15,43). Despite these suggestions, direct evidence of a low pH at the bone-resorbing lacuna underlying the osteoclast is still lacking and the acidification mechanisms are not yet elucidated.…”
mentioning
confidence: 99%
“…Recently, carbonic anhydrase inhibitors have been found to antagonize the calcemic response observed after administration of parathyroid hormone to nephrectomized rats (8) and the resorption of bone induced by parathyroid hormone in tissue cultures (9). These findings suggest an interaction of carbonic anhydrase inhibitors with the adenyl cyclase system of bone activated by parathyroid hormone.…”
Section: Introductionmentioning
confidence: 97%